Blue light-induced low mechanical stability of ruthenium-based coordination bonds: an AFM-based single-molecule force spectroscopy study - Muddassir, Mohd (RSC advances, 2020)
Metal complexes containing coordination bonds play a prominent role in many essential biological systems in living organisms. Examples of such complexes include hemoglobin containing iron, chlorophyll containing magnesium, and vitamin B 12 containing cobalt. Although the thermodynamic and other collective properties of metal complexes are well established, their mechanical stability remains minimally explored. Single-molecule force spectroscopy has been used to determine the structural and mechanical properties of chemical bonds; however, it has been minimally utilized in the field of coordination chemistry. Thus, here, we select a unique molecule of interest, HA-Ru II , {HA = hyaluronan and Ru II = [(bpy) 2 Ru(4-pyNH 2 ) 2 ](PF 6 ) 2 } and subject it to single-molecule force spectroscopy analysis to directly study its bond-rupture process. The molecule is excited by blue-light irradiation, and surprisingly, this whole process could be reversed without applying any external energy, such as heat or solvent exposure. Our results demonstrate the reversibility of the luminescent Ru II complex to its original state, a phenomenon that can be further applied to other coordination compounds. A HA-Ru II complex was conjugated to a hyaluronan polymer through amide bonds. In AFM experiments using the "multi-fishhook" approach, the cantilever tip made contact with the polymeric molecule, resulting in stretching, indicated by sawtooth-like force-extension curves.